2019
DOI: 10.1074/jbc.tm118.006295
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of fatty acids, nonsteroidal anti-inflammatory drugs, and coxibs with the catalytic and allosteric subunits of cyclooxygenases-1 and -2

Abstract: Edited by George M. CarmanProstaglandin endoperoxide H synthases-1 and -2, commonly called cyclooxygenases-1 and -2 (COX-1 and -2), catalyze the committed step in prostaglandin biosynthesis-the conversion of arachidonic acid to prostaglandin endoperoxide H 2 . Both COX isoforms are sequence homodimers that function as conformational heterodimers having allosteric (Eallo) and catalytic (Ecat) subunits. At least in the case of COX-2, the enzyme becomes folded into a stable Eallo/Ecat pair. Some COX inhibitors (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 63 publications
(90 reference statements)
0
50
1
3
Order By: Relevance
“…stearic and oleic acid) have the same effect on COX-1. Measurements of binding kinetics for these fatty acids indicate that their inhibition of COX-1 may not be due to competition with arachidonic acid for Ecat (15). These studies reveal a complex and isoform-dependent interplay between fatty acids and cyclooxygenases.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…stearic and oleic acid) have the same effect on COX-1. Measurements of binding kinetics for these fatty acids indicate that their inhibition of COX-1 may not be due to competition with arachidonic acid for Ecat (15). These studies reveal a complex and isoform-dependent interplay between fatty acids and cyclooxygenases.…”
Section: Discussionmentioning
confidence: 82%
“…These studies reveal a complex and isoform-dependent interplay between fatty acids and cyclooxygenases. In a recent review, Smith and Malkowski (15) conclude that cyclooxygenase activity is both pharmacologically and physiologically dependent on the fatty acid content and flavor of the membrane environment. MD simulation results presented here broaden our perspective on COX-1 binding to ER membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we found that omega-3 fish oil FAs and particularly eicosapentaenoic acid effectively inhibit the oxygenation of AA by binding Ecat of COX-1 but that eicosapentaenoic acid binds Eallo of COX-2 and has little effect on AA oxygenation by Ecat of COX-2 (56). As my scientific career comes to its conclusion, I feel very fortunate to have been involved in the discovery that COXs function as conformational heterodimers (1).…”
Section: At the University Of Michigan (2003-2016)mentioning
confidence: 89%
“…It involves the high flexibility of farnesol/FLS. The self-closing issue of membranes is of course also essential during mitosis, a process that requires Golgi activity (Smith and Malkowski, 2019).…”
Section: Paroulek and Sláma: In The Male Accessory Glands Of H Cecromentioning
confidence: 99%